2009
DOI: 10.1038/mt.2009.37
|View full text |Cite
|
Sign up to set email alerts
|

Glycoengineered Acid α-Glucosidase With Improved Efficacy at Correcting the Metabolic Aberrations and Motor Function Deficits in a Mouse Model of Pompe Disease

Abstract: Improving the delivery of therapeutics to disease-affected tissues can increase their efficacy and safety. Here, we show that chemical conjugation of a synthetic oligosaccharide harboring mannose 6-phosphate (M6P) residues onto recombinant human acid alpha-glucosidase (rhGAA) via oxime chemistry significantly improved its affinity for the cation-independent mannose 6-phosphate receptor (CI-MPR) and subsequent uptake by muscle cells. Administration of the carbohydrate-remodeled enzyme (oxime-neo-rhGAA) into Pom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(131 citation statements)
references
References 44 publications
6
120
1
4
Order By: Relevance
“…For the enzyme alone and combination therapy studies, Fabry mice were first immunotolerized to the recombinant human enzyme by treating the animals with a recombinant AAV vector encoding an inactive, but stable mutant form of α-Gal A (point mutation in amino acid 170). We and others have previously shown that AAVmediated hepatic-restricted expression of proteins resulted in the induction of immune tolerance to the expressed protein (22,(28)(29)(30)(31)(32). Administration of rh α-Gal A into AAV2/8 α-galD170Mut-treated Fabry mice did not elicit antibodies to the enzyme (data not shown).…”
Section: Combination Therapy With Genz-682452 and α-Galactosidase A Imentioning
confidence: 94%
“…For the enzyme alone and combination therapy studies, Fabry mice were first immunotolerized to the recombinant human enzyme by treating the animals with a recombinant AAV vector encoding an inactive, but stable mutant form of α-Gal A (point mutation in amino acid 170). We and others have previously shown that AAVmediated hepatic-restricted expression of proteins resulted in the induction of immune tolerance to the expressed protein (22,(28)(29)(30)(31)(32). Administration of rh α-Gal A into AAV2/8 α-galD170Mut-treated Fabry mice did not elicit antibodies to the enzyme (data not shown).…”
Section: Combination Therapy With Genz-682452 and α-Galactosidase A Imentioning
confidence: 94%
“…Receptor-mediated uptake of GAA, like other lysosomal enzymes, occurs mainly through a receptor-mediated endocytosis mechanism using CI-MPR, 22,23 and clenbuterol treatment during ERT or gene therapy increased CI-MPR expression in the skeletal muscle of GAA-KO mice with positive therapeutic effects. 11,13 In this study, clenbuterol significantly increased the expression of CI-MPR in skeletal muscle (Fig.…”
Section: Ci-mpr Expression Is Increased By Gaa Expressionmentioning
confidence: 99%
“…A comparable reduction of glycogen level was obtained in heart and diaphragm using a 8-fold lower dose, and in skeletal muscle using a 4-fold lower dose. The oxime-neo-rhGAA variant displayed higher stability, increased affinity for the CI-MPR, and approximately 5-fold higher efficacy at clearing glycogen with only one-fifth the dose of unmodified enzyme (67). Interestingly, the oxime-neorhGAA generated a more rapid clearance of glycogen thereby reducing or minimizing muscle damage.…”
Section: Enzyme Modification and Enhanced Deliverymentioning
confidence: 99%
“…This hypermannose-6-phosphorylated enzyme (HP-GAA) was no more effective at clearing glycogen from Pompe mice than the unmodified enzyme, due to a sequestration by mannose receptors on endothelial cells and macrophages (66). Synthetic oligosaccharides carrying mannose-6-phosphate residues were then conjugated to the rhGAA using carbonyl/hydrazide (neorhGAA) or carbonyl/oxime-mediated chemistry (oxime-neorhGAA) (66,67). The resulting neo-rhGAA enzyme displayed near normal specific activity, increased affinity for the CI-MPR, and was internalized 20-fold more efficiently than the naïve enzyme into myoblasts in vitro.…”
Section: Enzyme Modification and Enhanced Deliverymentioning
confidence: 99%